A novel gene signature based on five immune checkpoint genes predicts the survival of glioma - Wei Zhang; You Zhai; Guanzhang Li; Tao Jiang (Chinese Neurosurgical Journal, 2021)
Abstract Background Glioma is the most common and fatal type of nerve neoplasm in the central nervous system. Several biomarkers have been considered for prognosis prediction, which is not accurate enough. We aimed to carry out a gene signature related to the expression of immune checkpoints which was enough for its performance in prediction. Methods Gene expression of immune checkpoints in TGGA database was filtrated. The 5 selected genes underwent verification by COX and Lasso-COX regression. Next, the selected genes were included to build a novel signature for further analysis. Results Patients were sub-grouped into high and low risk according to the novel signature. Immune response, clinicopathologic characters, and survival showed significant differences between those 2 groups. Terms including “naive,” “effector,” and “IL-4” were screened out by GSEA. The results showed strong relevance between the signature and immune response. Conclusions We constructed a gene signature with 5 immune checkpoints. The signature predicted survival effectively. The novel signature performed more functional than previous biomarkers.